1999
DOI: 10.1074/jbc.274.38.26705
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 2C Inactivates F-actin Binding of Human Platelet Moesin

Abstract: During activation of platelets by thrombin phosphorylation of Thr558 in the C-terminal domain of the membrane-F-actin linking protein moesin increases transiently, and this correlates with protrusion of filopodial structures. Calyculin A enhances phosphorylation of moesin by inhibition of phosphatases. To measure this moesin-specific activity, a nonradioactive enzymelinked immunosorbent assay method was developed with the synthetic peptide Cys-Lys 555 -Tyr-Lys-Thr(P)-Leu-Arg 560 coupled to bovine serum albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…Unfolding of the molecule into an active conformation occurs following binding to phosphoinositides and phosphorylation of the C-terminal threonine (T558 in moesin, T567 in ezrin, T564 in radixin) (Fievet et al, 2004). The open molecules bind with various membrane proteins (Tsukita et al, 1994;Bretscher et al, 1997;Reczek et al, 1997;Simons et al, 1998;Yonemura et al, 1998) at the N-terminal region and F-actin through the C-terminal domain Hishiya et al, 1999;Pearson et al, 2000). As osteosarcoma cells in culture express high levels of ezrin and phosphorylated ERM, it was possible that the high levels of phosphorylated ERM seen in single cells that arrived in the lung following tail vein injection was merely a residual effect of their growth in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Unfolding of the molecule into an active conformation occurs following binding to phosphoinositides and phosphorylation of the C-terminal threonine (T558 in moesin, T567 in ezrin, T564 in radixin) (Fievet et al, 2004). The open molecules bind with various membrane proteins (Tsukita et al, 1994;Bretscher et al, 1997;Reczek et al, 1997;Simons et al, 1998;Yonemura et al, 1998) at the N-terminal region and F-actin through the C-terminal domain Hishiya et al, 1999;Pearson et al, 2000). As osteosarcoma cells in culture express high levels of ezrin and phosphorylated ERM, it was possible that the high levels of phosphorylated ERM seen in single cells that arrived in the lung following tail vein injection was merely a residual effect of their growth in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation at T567 in ezrin (the homologous sites are T564 in radixin and T558 in moesin) has received a great deal of attention because this phosphorylation event is believed to open up the NH 2 terminal-to-COOH terminal (N-C) binding of ezrin, tranforming ezrin into an active state with accessible domains for binding to membrane and F-actin. In vitro experiments with platelet moesin have indicated that T558 phosphorylation is necessary for binding to F-actin (16,23). The increased affinity to F-actin is not likely due to the phosphate group itself, because COOH terminal radixin fragments bind to F-actin with similar efficiencies, whether phosphorylated on T564 or not (22).…”
mentioning
confidence: 98%
“…Recent studies have shown that phosphorylation of the moesin, ezrin, and radixin family of proteins is required for mediation of actin cross-linking to the PM (22,23). To induce phosphorylation-dependent association of the actinbinding proteins with the PM we treated human platelets with calyculin A, a serine/threonine phosphatase inhibitor that inhibits protein phosphatases 1 and 2 (11,23).…”
Section: Effect Of Cyt D and Jp On Preactivated Store-mediated Ca 2ϩmentioning
confidence: 99%